2017
DOI: 10.1093/nar/gkx549
|View full text |Cite
|
Sign up to set email alerts
|

XIAP upregulates expression of HIF target genes by targeting HIF1α for Lys63-linked polyubiquitination

Abstract: The cellular response to hypoxia is characterised by a switch in the transcriptional program, mediated predominantly by the hypoxia inducible factor family of transcription factors (HIF). Regulation of HIF1 is primarily controlled by post-translational modification of the HIF1α subunit, which can alter its stability and/or activity. This study identifies an unanticipated role for the X-linked inhibitor of apoptosis (XIAP) protein as a regulator of Lys63-linked polyubiquitination of HIF1α. Lys63-linked ubiquiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…K63-linked polyubiquitination of HIF-1α catalyzed by TRAF6 can protect it from degradation [146]. XIAP modifies HIF-1α by K63-linked polyubiquitination to promote its nuclear retention and enhance HIF-dependent gene expression [147]. In conclusion, ubiquitination is an important regulatory mechanism of HIF-1.…”
Section: Ubiquitination and Transcription Factorsmentioning
confidence: 93%
“…K63-linked polyubiquitination of HIF-1α catalyzed by TRAF6 can protect it from degradation [146]. XIAP modifies HIF-1α by K63-linked polyubiquitination to promote its nuclear retention and enhance HIF-dependent gene expression [147]. In conclusion, ubiquitination is an important regulatory mechanism of HIF-1.…”
Section: Ubiquitination and Transcription Factorsmentioning
confidence: 93%
“…Cells were lysed in 8 M urea lysis buffer and immunoblotted as described ( 21 ). Antibodies used were HIF1α (Clone 241809, R&D systems), HIF2α (#7096, Cell Signaling Technologies), phospho- eIF2α (Ser 51) (#9721, Cell Signaling Technologies), eIF2α (#5324, Cell Signaling Technologies), PERK (#3192, Cell Signaling Technologies), YB-1 (A303–231A, Bethyl), β-tubulin (#2146, Cell Signaling Technologies), VHL (#68547, Cell Signaling Technologies), β-actin (AC-74, Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…It was found that apoptotic nuclei could be seen in the muscle tissue of dermatomyositis, and the expression of apoptotic factors was upregulated, suggesting that apoptotic cells might be involved in the pathological process of dermatomyositis. [ 42 ] XAF1-related excessive apoptosis may exist in dermatomyositis, which may be one of the causes of dermatomyositis. [ 43 ]…”
Section: Discussionmentioning
confidence: 99%